The F# Language Design RFCs (F# 4.0, 4.1) - Syme, Don; Parkinson, Matthew J. (The F# Software Foundation Core Engineering Group, 2017)
RFCs and docs related to the F# language design process. Collaboratively reviewed and edited by multiple contributors. For RFCs that were implemented in F# 4.0, see the F# 4.0 RFCs For RFCs that were implemented in F# 4.1, see the F# 4.1 RFCs